Penguatan Peran Administrasi dalam Mendorong Partisipasi Masyarakat pada Kegiatan Kerja Bakti di Kampung Nendali - Rahmat Nurjaman (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to strengthen the role of administration in increasing community participation in community service activities in Nendali Village, East Sentani District, Jayapura Regency. So far, community activities in the village have been carried out informally without an orderly administration system, making it difficult to evaluate and sustain activities. Through a participatory approach, this activity invites residents to be directly involved in community service to clean the environment and participate in discussion sessions on the importance of simple recording in social activities. The results of the activity show an increase in community awareness of the importance of administration, marked by the use of attendance lists, meeting minutes, and activity documentation. In addition, this activity also encourages a more organized and transparent spirit of mutual cooperation. Analysis of community involvement shows that administration has a significant influence in forming a sense of responsibility and social accountability at the community level. The challenges faced include limited time for residents and understanding of administration, but can be overcome through a practical and educational approach. This activity has positive implications and can be replicated in other villages with similar conditions.